Tantangan Dan Peluang Pemanfaatan Teknologi Informasi Dalam Pembelajaran Online Masa Covid-19 - Ni Komang Suni Astini (Jayapangus Press, 2020)
This study was conducted to determine the challenges and opportunities for the use of information technology on online learning in STKIP Agama Hindu Amlapura during the Covid-19 pandemic. By using library research methods and survey methods. The samples used in this study were all college students of STKIP Agama Hindu Semester II and Semester IV. The Covid-19 pandemic give a influenced college in Indonesia including the STKIP Agama Hindu Amlapura with Enforcement of physical distancing policy which then becomes the basis of the implementation of online lectures, by using information technology. The most widely used media in online learning at STKIP Agama Hindu Amlapura are Whatshap group and Google Classroom because these application is very easy to use. But there are some problem such as the lacking facilities. Based on the survey results, 50% of students do not have a laptops, and 80% of students are difficult to get signals and wasteful in using a data plan because many students live far from urban areas. The study was not effective because as many as 61.5% of students stated they never used online learning media before the co-19 pandemic. But the fact by using online learning is a trigger for the acceleration of the process of digital transformation of Indonesian education. Before pandemic some of discourse, supporting policies, and socialization about the era of education 4.0 was not successful. But Covid-19 give an extraordinary impact on digital transformation towards the educational era 4.0.